2018
DOI: 10.1016/j.tcs.2017.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Minimum connected transversals in graphs: New hardness results and tractable cases using the price of connectivity

Abstract: Abstract. We perform a systematic study in the computational complexity of the connected variant of three related transversal problems: Vertex Cover, Feedback Vertex Set, and Odd Cycle Transversal. Just like their original counterparts, these variants are NP-complete for general graphs. A graph G is H-free for some graph H if G contains no induced subgraph isomorphic to H. It is known that Connected Vertex Cover is NP-complete even for H-free graphs if H contains a claw or a cycle. We show that the two other c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 24 publications
(64 citation statements)
references
References 31 publications
(38 reference statements)
2
62
0
Order By: Relevance
“…For every s ≥ 1, Vertex Cover (by combining the results of [1,34]) and Connected Vertex Cover [10] are polynomial-time solvable on sP 2 -free graphs. 4 Moreover, Vertex Cover is also polynomial-time solvable on (sP 1 + P 6 )-free graphs, for every s ≥ 0 [20], as is the case for Connected Vertex Cover on (sP 1 + P 5 )-free graphs [24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For every s ≥ 1, Vertex Cover (by combining the results of [1,34]) and Connected Vertex Cover [10] are polynomial-time solvable on sP 2 -free graphs. 4 Moreover, Vertex Cover is also polynomial-time solvable on (sP 1 + P 6 )-free graphs, for every s ≥ 0 [20], as is the case for Connected Vertex Cover on (sP 1 + P 5 )-free graphs [24].…”
Section: Introductionmentioning
confidence: 99%
“…Grigoriev and Sitters [18] proved that Connected Feedback Vertex Set is NP-complete even on planar graphs with maximum degree 9. More recently, Chiarelli et al [10] proved that Connected Odd Cycle Transversal is NP-complete even on graphs of arbitrarily large girth and on line graphs.As all three decision problems and their connected variants are NP-complete, we can consider how to restrict the input to some special graph class in order to achieve tractability. Note that this approach is in line with the aforementioned results in the literature, where NP-completeness was proven on special graph classes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This leads us to the research question of our paper: For which classes of graphs do the complexities of Vertex Cover and Connected Vertex Cover coincide? This question was addressed by Chiarelli et al [6] who considered classes of graphs characterized by a single forbidden induced subgraph H. Such graphs are called H-free. They observed that the results of Munaro [16] imply that Connected Vertex Cover is NP-complete for H-free graphs if H contains a cycle or a claw.…”
Section: Connected Vertex Covermentioning
confidence: 99%
“…By using the concept of the price of connectivity [3,5,12], Chiarelli et al [6] proved that Connected Vertex Cover is polynomial-time solvable for sP 2free graphs for any integer s ≥ 1. For Vertex Cover this follows by combining two classical results [2,19] (as is well-known).…”
Section: Connected Vertex Covermentioning
confidence: 99%